The usability and applicability of knowledge translation theories, models, and frameworks for research in the context of a national health service - Virginia Minogue; Karen Matvienko-Sikar; Catherine Hayes; Mary Morrissey; Gregory Gorman; Ana Terres (BMC, 2021)
Abstract Background Translating research findings into service improvements for patients and/or policy changes is a key challenge for health service organizations. The Health Service Executive (HSE) in Ireland launched the Action Plan for Health Research 2019-2029, as reported by Terrés (HSE, Dublin, 2019), one of the goals of which is to maximize the impact of the research that takes place within the service to achieve improvements in patient care, services, or policy change. The purpose of this research is to review the literature on knowledge translation theories, models, and frameworks (TMFs) and to assess the suitability of the TMFs for HSE use, selecting one or more for this purpose. The aim is to produce guidance for HSE researchers and other health services staff, validate the usability of the framework(s) with researchers, and review and implement the guidance. It was hoped that identifying a suitable methodology would provide the means to increase the uptake and application of research findings, and reduce research wastage. This paper reports on the first part of the study: the review, assessment, and selection of knowledge translation TMFs for a national health service. Methods An interdisciplinary working group of academic experts in implementation science, research wastage, and knowledge translation, along with key representatives from research funders (Health Research Board) and HSE personnel with expertise in quality improvement and research management, undertook a three-stage review and selection process to identify a knowledge translation TMF that would be suitable and usable for HSE purposes. The process included a literature review, consensus exercise, and a final consensus workshop. The review group adopted the Theory Comparison and Selection Tool (T-CaST) developed by Birken et al. (Implement Sci 13: 143, 2018) to review knowledge translation theories, models, and frameworks. Results From 247 knowledge translation TMFs initially identified, the first stage of the review identified 18 that met the criteria of validity, applicability, relevance, usability, and ability to be operationalized in the local context. A further review by a subgroup of the working group reduced this number to 11. A whole-group review selected six of these to be reviewed at a facilitated consensus workshop, which identified three that were suitable and applicable for HSE use. These were able to be mapped onto the four components of the HSE knowledge translation process: knowledge creation, knowledge into action, transfer and exchange of knowledge, and implementation and sustainability. Conclusion The multiplicity of knowledge translation TMFs presents a challenge for health service researchers in making decisions about the appropriate methods for disseminating their research. Building a culture that uses research knowledge and evidence is important for organizations seeking to maximize the benefits from research. Supporting researchers with guidance on how to disseminate and translate their research can increase the uptake and application of research findings. The use of robust selection criteria enabled the HSE to select relevant TMFs and develop a process for increasing the dissemination and translation of research knowledge. The guidance developed to inform and educate researchers and knowledge users is expected to increase organizational capacity to promote a culture of research knowledge and evidence use within the HSE.